Sierra Leone : Enhanced Heavily Indebted Poor Countries Initiative; Completion Point Document and Multilateral Debt Relief Initiative. (IMF Staff Country Reports; Country Report ;, 2007)
This paper explains Sierra Leone's completion point under the Enhanced Initiative for Heavily Indebted Poor Countries (HIPC) and debt relief under the Multilateral Debt Relief Initiative (MDRI). With enhanced HIPC and MDRI assistance, Sierra Leone will achieve a debt profile below the HIPC threshold. Assurances have been obtained regarding participation in the enhanced HIPC Initiative from creditors representing more than 81 percent of the relief to be provided. The sensitivity analysis shows that Sierra Leone's external debt sustainability could be jeopardized by adverse shocks and financing on nonconcessional terms.